The Effect of Honey on Granulating Tissue of The Mandibular Bone - Harsono, Anastasia Dessy; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Background: For many years, ancient civilizations used honey to heal wounds. Rediscovery of honey by modern physicians its use in conventional medicine. Few detailed descriptions of honey in healing difficult surgical wounds have been previously published.Methods: We report patient, male, 16 years old, who suffered acute lymphocytic leukemia and extensive mandibular eschar and had presented half of mandible bone exposed after escharectomy. Given the of closing the defect due to poor general condition of the patient, we advocated to applicate honey dressing on mandible bone to promote granulation tissue, to prevent infection and to promote epithelialization.Results: Due to honey’s effect are anti inflammatory and antimicrobial activity, promotes debridement, reduces malodor, maintains moist wound environment, and stimulates healing, in a month, all mandible exposed had been covered by granulation tissue, followed by skin grafting.Conclusion: In this case, honey had been proven effectively to stimulate granulation tissue growth on mandible bone both before and after surgery.